Cytoplasmic DAXX drives SQSTM1/p62 phase condensation to activate Nrf2-mediated stress response - Yi Yang (Nature Portfolio, 2019)
The autophagy protein p62 undergoes liquid-liquid phase separation but how this is regulated is unclear. Here, the authors report that the histone chaperone DAXX interacts with p62 in the cytoplasm to drive its phase separation.